The traditional bio-medical dichotomy in search of a common ground - M. L. Arthur (AOSIS, 1997)
Differences between bio-medical and traditional systems are regarded as irreconcilable by many, including members of the medical, nursing and allied professions. This article explores those areas in which emphasis on difference has resulted in an exclusion of the common basis from which culturally determined areas of human and health behaviours are derived. As long as difference is emphasized to the exclusion of attempts to find a common ground, the dichotomy between traditional and bio-medicine will remain.